Law Enforcement of Khalwat under the Aceh Jinayat Qanun: A Study in Langsa City - Muhammad Suhardi; Muhammad Daffa Fahrezi (Yayasan Hisnul Muslim Lombok, 2025)
The implementation of Islamic criminal law in Aceh represents a distinctive legal phenomenon within Indonesia’s unitary state system, particularly through the enforcement of Aceh Qanun Number 6 of 2014 concerning Jinayat Law. One form of offense regulated under this qanun is khalwat, which is regarded as a moral violation with potential social consequences. Despite the existence of a clear legal framework, violations of khalwat continue to occur, indicating challenges in law enforcement at the local level. This study aims to analyze the enforcement of khalwat regulations by the Civil Service Police Unit (Satuan Polisi Pamong Praja) in Langsa City, identify supporting and inhibiting factors, and examine the efforts undertaken to overcome enforcement obstacles. This research employs a qualitative descriptive-analytical approach. Data were collected through in-depth interviews with law enforcement officers and relevant stakeholders, direct observation of enforcement practices, and documentation analysis of legal and institutional records. Data were analyzed thematically using an interactive model, supported by law enforcement theory and Islamic legal principles. Data triangulation was applied to ensure the validity and credibility of the findings. The findings reveal that khalwat enforcement in Langsa City has been conducted in accordance with existing legal provisions through patrols, supervision, and case handling procedures. However, enforcement remains inconsistent due to limited human resources, inadequate logistical support, and budgetary constraints. Socio-cultural factors, including varying public perceptions and resistance toward enforcement actions, further hinder effectiveness. In response, Satpol PP has implemented several strategic measures, including capacity building, community engagement, public legal education, and strengthened interagency coordination. This study concludes that effective enforcement of khalwat regulations requires more than coercive legal measures. A holistic approach that integrates legal certainty, institutional capacity, and socio-cultural engagement is essential to enhance compliance and legitimacy. Strengthening legal awareness, improving resource allocation, and fostering community participation are critical for the sustainable enforcement of Islamic criminal law in Aceh.